Influence of Non-protein Diets on Hepatic Metabolism and Endocrine in Barramundi (Lates calcarifer) - Fu, Zhengyi; Zhou, Shengjie; Yu, Gang; Yang, Rui; Han, Mingyang; Ma, Zhenhua (Frontiers in Marine Science, 2021)
This study evaluated the effects of different dietary non-protein energy sources on hepatic metabolism and endocrine of barramundi. Fish were fed iso-energy diets (18 MJ kg–1) with two types of non-protein energy source in the experimental group and a regular diet was used as the control. The feeding trial lasted 56 days. In the present study, CPT1 and SCD expression in fish fed high lipid diet were upregulated and liver lipid metabolism was more active than the control group. Serum biochemical parameters including serum glucose, serum triacylglycerol and serum cholesterol were significantly increased. The IGF-I and IGF-II expressions were significantly upregulated, and growth performances were improved in fish fed the high lipid diet. When barramundi were fed with the high carbohydrate diet, GK expression was downregulated and cPEPCK expression was upregulated, indicating that glycogen might accumulate in liver. The fluctuation of serum biochemical parameters and the growth performance were not significantly different compared to the control group. In conclusion, high lipid diet can shorten the raising period, but it causes the change of metabolic level and the increase of useless adipose tissue; The high carbohydrate diet did not significantly improve the growth performance, and no significant metabolic abnormalities were observed, indicating that carbohydrate has the potential to be the feed energy supply source for juvenile barramundi. The results provide insights for further understanding the availability of non-protein energy sources in the diet of juvenile barramundi.